The state must compete: Optimal pricing of legal cannabis. (22nd November 2019) - Childs, Jason; Stevens, Jason
Abstract: We examine the socially optimal pricing strategy for the legal cannabis industry that faces significant competition from an illicit market. We explore the impact of different preferences for legal and illicit cannabis using a constant elasticity of substitution utility function. We find that under a range of policy objectives and other circumstances, the socially optimal pricing strategy is for the legal market price to be dramatically lower than the illicit market price. This contradicts the approach taken across Canada in the year since legalization. These findings suggest that governments should adopt policies to reduce the price of legal cannabis. Sommaire: Nous étudions la stratégie de prix optimale pour la société en ce qui concerne le marché légal du cannabis, face à la compétition considérable d'un marché clandestin. Nous examinons l'impact des différentes préférences pour le cannabis légal et illicite en utilisant une fonction utilitaire d'élasticité de substitution constante. Nous découvrons que selon une gamme d'objectifs stratégiques et autres circonstances, la stratégie de prix optimale pour la société est que le prix du marché légal soit nettement inférieur à celui du marché illicite. Cela entre en contradiction avec l'approche adoptée à travers tout le Canada durant l'année après la légalisation. Ces résultats indiquent que les gouvernements doivent adopter des politiques visant à diminuer le prix du cannabis légal.